Multi-renewable management: Interactions between wind and solar within uncertain technology ecological system. (1st May 2019) - Du, Yongqiang; Song, Bingjie; Duan, Hongbo; Tsvetanov, Tsvetan G.; Wu, Yingying
Highlights: A stochastic technology interaction framework is developed in this work. Differentiated scale-dependence effects are identified for wind and solar markets. Technology interactions are dominated by mutualism and prey-predator types. Stochastic technology diffusion orbits closely relates to deterministic equilibrium. Mean tech-orbits of random orbits converges to the analytic equilibrium orbits. Abstract: By using stochastic Lotka-Volterra model, we make a cross-country analysis to potential interactions between penetrations of wind and photovoltaic (PV) technology within uncertain technology ecological systems, and explore the possible distributions of stochastic technology proliferation orbits. We find both positive and negative scale effects for wind markets, while PV solar markets are consistently scale-restrictive for all the target countries; the current technology interactions are dominated by mutualism and prey-predator types, of which prey-predator relationships mainly exist in the US, China and Italy, with PV solar to be predators. Most importantly, we find significant relationships between stochastic technology diffusion orbits and deterministic technology equilibrium orbit; specifically, random orbits of cumulative installed capacity for both wind and PV solar oscillate around the equilibrium orbit under the deterministic Lotka-Volterra model, normally distributed, and the mean orbit of such large-scale random orbits converges to the analytic equilibrium orbit. This finding makes great sense to identify countries with stable technology diffusion distributions, and contributes to exploit predictive features of stochastic Lotka-Volterra model. On this basis, we recognize 3 countries with normally distributed random orbits of technology penetration, i.e., India, Japan and Italy, and three-year forecasts to 2020 are provided for both wind and PV solar technology.